PENGARUH PENGGUNAAN LIMBAH BETON SEBAGAI SUBSTITUSI AGREGAT KASAR TERHADAP KUAT TEKAN BETON - Nusantara, Agung; Mulyati, Ely (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to The Effect of Using Concrete Waste as a Coarse Aggregate Substitute on Concrete Compressive Strength. To find out whether concrete waste can be used as a good coarse aggregate substitute in Fc` 26.4 MPa concrete. And To find out how much compressive strength value is produced using concrete waste. At all test ages (7, 14, and 28 days), the concrete mixture with 30% concrete waste showed a consistent increase in compressive strength compared to normal concrete. This shows that the use of concrete waste as a coarse aggregate substitute with a percentage of 30% can increase the compressive strength of Fc 26 MPa concrete. Variations in the mixture of 10% and 70%, concrete waste did not provide better compressive strength results compared to normal concrete. Even the percentages of 10% and 70% tend to reduce the compressive strength of concrete. This study shows that the use of concrete waste as a coarse aggregate substitute in Fc 26 MPa concrete provides variations in the compressive strength of concrete at the ages of 7, 14, and 28 days. Specifically, the variation of 30% waste concrete mixture resulted in an increase in the compressive strength of concrete compared to normal concrete at each test age. At the age of 7 days, the compressive strength of normal concrete was 17.12 MPa, while the compressive strength with 10% LB was 16.94 MPa, 30% LB was 17.69 MPa and 70% LB was 16.60 MPa. At the age of 14 days, the compressive strength of normal concrete was 22.79 MPa, while the compressive strength with 10% LB was 21.73 MPa, 30% LB was 23.22 MPa and 70% LB was 21.52 MPa. At the age of 28 days, the compressive strength of normal concrete was 25.78 MPa, while the compressive strength with 10% LB was 25.17 MPa, 30% LB was 26.53 MPa and 70% LB was 24.96 MPa.Keywords: Concrete, Aggregate, Compressive Strength.